Канонічна форма многочленних матриць з усіма рівними елементарними дільниками - Шаваровський, Б.З. (Український математичний журнал, 2012)
Исследуется задача приведения многочленных матриц к каноническому виду посредством полускалярно эквивалентных преобразований. Выделен один класс многочленных матриц, для которого указана каноническая форма относительно полускалярной эквивалентности. Последняя дает возможность решать задачу классификации наборов матриц над полем с точностью до подобия. The problem of reducing polynomial matrices to the canonical form by using semiscalar equivalent transformations is studied. A class of polynomial matrices is singled out, for which the canonical form with respect to semiscalar equivalence is indicated. This form enables one to solve the classification problem for collections of matrices over a field up to similarity.